Bahasa Sebagai Simbolisasi Mempertahankan Kekuasaan - Sofyan, Nur (Interaksi: Jurnal Ilmu Komunikasi, 2014)
The language has an important role in a power. The relation of language and power had existed centuries ago. Language not only reflects the social status, but more than that. The language is used as the symbol of maintaining power. World leaders use the speech as a tool to legitimize power. This is apparent from the order of the sentences and the way they played a series of issues in his speech. As it was done by President, State leaders or a King. Power requires its own way to maintain legitimacy. So the language is viewed can be used as a tool and a symbol of maintaining power. In Javanese language used as a means to differentiate the social classes among the nobility and common people. Blatantly disrespectful language should only be used by those who are included on the nobility. As for the political scene and domination, the language used by President Bush in an effort justification of effort in Kuwait attack upon himself and his allies. While President Susilo Bambang Yudhoyono used a speech to the language to clarify the truth of the case of Century Bank. This was done as an attempt to preserve his power by giving information about the sat question. This article truly wanted to give an explanation on the application form of the language as a symbol of the mass and retain power. Through a series of speeches a leader can play a social issue. At the end of this article the author created to provide shared understanding that the potential of the language and symbols of power have been known to the authorities in maintaining his rule until this time.